L’écriture du breton dans l’histoire. Essai de synthèse - Yves Le Berre (La Bretagne Linguistique, 1991)
The history of Breton writing extends over six and a half centuries, from the few sentences dating from the middle of the fourteenth century and constituting what is known as "Ivonet Omnès Breton" to the present day. It was born of the need for a given social group to produce written material in Breton, before it lost its raison d’être because of the expansion of French. After the widespread use of French in the mid-twentieth century, the logic would have it that Breton writing, in the absence of an obliged clientele, would live its last hours. However, the number of original texts and translations published each year in Breton does not decrease. The nature of this written language is, however, quite different from that which was previously used.